A coupled finite difference mooring dynamics model for floating offshore wind turbine analysis. (15th August 2018) - Chen, Lin; Basu, Biswajit; Nielsen, Søren R.K.
Abstract: This study develops a coupled nonlinear hydrodynamic model of a mooring system consisting of multiple cables for analyses of floating offshore wind turbines (FOWTs). The model is based on a finite difference model of submerged cables which considers cable-seabed interaction, current effect, cable bending and torsional stiffness. The implementation of the model proposes a parallelization scheme for solving the cable responses to improve the computational efficiency. The developed program is then coupled with a spar type FOWT and verified using an experimentally validated open source mooring simulation program. Furthermore, the model is used to study the impact of nonlinear dynamics of the mooring system on FOWT responses in the presence of current. Both static responses of a spar FOWT under current load and dynamic responses of the spar FOWT under wind, wave and current loads are investigated. Responses are compared where varied mooring models are used including the linear model, quasi-static model and nonlinear mooring models without and with current effect on cables considered. The results show that the current effect on cables can have a considerable impact on the restoring effect of the mooring system and hence the spar and cable responses. The current effect on mooring cables needs to be properly considered in the FOWT analysis. Highlights: A finite difference model is proposed for coupled analysis of floating offshore wind turbines. Parallel computation is implemented for solving dynamics of multiple cables in a mooring system. The developed mooring dynamics code is verified with a lumped mass model. The coupled model is used for analysis of a spar-type floating offshore wind turbine.